2019
DOI: 10.1038/s41467-019-08727-8
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of cooperation through reputation and group polarization

Abstract: Humans exhibit a remarkable capacity for cooperation among genetically unrelated individuals. Yet, human cooperation is neither universal, nor stable. Instead, cooperation is often bounded to members of particular groups, and such groups endogenously form or break apart. Cooperation networks are parochial and under constant reconfiguration. Here, we demonstrate how parochial cooperation networks endogenously emerge as a consequence of simple reputation heuristics people may use when deciding to cooperate or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 70 publications
4
63
0
Order By: Relevance
“…Intergroup conflict has been an unfortunate constant throughout human history, from intergroup violence in ancestral hunter-gatherer societies to modern warfare (Campbell 1972; 1975). For group conflict, collective action and coordination are needed, and theoretical models suggest that cooperation and coordination may have indeed coevolved with conflict (Choi & Bowles 2007; Fu et al 2012; Gross & De Dreu 2019b; Konrad & Morath 2012; Masuda 2012; Nowak et al 2010; Rusch 2014a; 2014b; Traulsen & Nowak 2006). The coevolution of cooperation and conflict may explain why cooperation is often in-group bounded and parochial (Balliet et al 2014; Gross & De Dreu 2019b; Bernhard et al 2006; Bowles 2009; Choi & Bowles 2007; De Dreu et al 2010; Efferson et al 2008; Garcia & Van den Bergh 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intergroup conflict has been an unfortunate constant throughout human history, from intergroup violence in ancestral hunter-gatherer societies to modern warfare (Campbell 1972; 1975). For group conflict, collective action and coordination are needed, and theoretical models suggest that cooperation and coordination may have indeed coevolved with conflict (Choi & Bowles 2007; Fu et al 2012; Gross & De Dreu 2019b; Konrad & Morath 2012; Masuda 2012; Nowak et al 2010; Rusch 2014a; 2014b; Traulsen & Nowak 2006). The coevolution of cooperation and conflict may explain why cooperation is often in-group bounded and parochial (Balliet et al 2014; Gross & De Dreu 2019b; Bernhard et al 2006; Bowles 2009; Choi & Bowles 2007; De Dreu et al 2010; Efferson et al 2008; Garcia & Van den Bergh 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Much like contemporary conflict theory, models on the coevolution of conflict, coordination, cooperation, and institution formation assume symmetric games of conflict. For example, evolutionary agent-based simulations are mostly grounded in N- person Prisoner's Dilemma games or, in some cases, symmetric games of Chicken or Stag Hunt (Choi & Bowles 2007; Gross & De Dreu 2019b; Traulsen & Nowak 2006). If conflict is indeed the “midwife of altruism” (Bowles 2009), we should, however, take into account that conflict has often two faces, attack and defense, with distinct success functions and distinctly different social dynamics and institutional requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Aarøe and Petersen (2018) found that episodic content of news stories about social welfare (i.e., content about specific welfare recipients) was communicated in greater detail than thematic content (i.e., generalized, statistical facts about welfare recipients). More generally, evidence from economic games shows that gossiping about the self-interested actions of others is key for upholding cooperation and obtaining optimal outcomes in social groups (Gross and Dreu 2019). From this perspective, the inclination to gossip evolved specifically to expose and counteract selfinterested individuals and keep up cooperation in social groups (Dunbar 2004).…”
Section: Complicit Citizens: An Interpersonal Transmission Bias Favormentioning
confidence: 99%
“…In Gross and De Dreu (2019), players do not observe previous actions of others, but can exchange opinions and apply reputation heuristics in line with balance theory, based on their private experience and the private experience of the players from whom they obtain an opinion. The authors consider both players with 'friendship heuristics', who consider only the opinion of players who have been friendly to them ('the friend of my friend is my friend' and 'the enemy of my friend is my enemy'), and players with 'Heider heuristics', who additionally consider the opinion of players who have been unfriendly to them ('the friend of my enemy is my enemy' and 'the enemy of my enemy is my friend').…”
Section: Indirect Reciprocitymentioning
confidence: 99%